A interpretação no Direito Tributário sob o viés da semiótica comunicacional - Washington, Eliane Aparecida Dorico (2019)
This study seeks to use semiotics as a method for interpreting Tax Law, but specifically the Leading Case Extraordinary Resource no. 574706, judged by the Federal Supreme Court and making its final decision on October 2, 2017. On that date the Judgement of the Extraordinary Recourse (RE) 574706, in which the Supreme Court had decided by a majority of votes for the exclusion of the Circulation of Merchandise and Services Tax (ICMS) based on the calculation of the contributions for Social Integration Program (PIS) and the contribution for Social Security Financing (COFINS), and the only and principal General Repercussion. This is recognized because there are various lawsuits being processed about this same subject matter which encompasses all of these suits and which are deadlockng the courts and the Complementary Law 70/91. The object of this study is to give clarity and to serve as an efficient instrument in interpreting tax law seeing the effectiveness and agility of the Courts through the communicational process. In other words, this project seeks to prove the importance of Piercian semiotics in the interpretation of tax law to explain the possibility of phenomenology of tax incidence and to ascertain quantum debeatur of PIS/COFINS, these taxes which are charged on every consumer product. This justifies the correlation of Semiotics and Tax Law in order that there can be a constant update of the normative process accompanying social evolution. Consequently, the speedy results of similar cases in diverse instances can be done via an effective communicational process. Thus, the existing correlation between three sciences will be proposed: Law, Communication and Semiotics, in this, the relevance of Semiotics is implied for both Communication and Law. Such an approach is necessary in order that there is effective communication between the cases and judgements and as well to shorten the time it takes for a case to complete its run through the courts. This will also facilitate communication among the organs of different instances in the effective judicial provisions